Studi Reproduksi dan Morfometri Ikan Sembilang (Plotosus canius) Betina yang Didaratkan di Pengepul Wilayah Krobokan Semarang - Dewanti, Yustin Ragil; Irwani, Irwani; Redjeki, Sri (977-2407769)
One of the fish part of family Plotosidae are Sembilang. This marine fish are usually consumed by the peoples as smoked fish. Peoples know well this fish became of their good teste and has quite nutritious. Although Sembilang not been many studied, but research on aspects of reproduction and morphometry of Sembilang is necessary to prevent the decline in this fish populations. The research was conducted in October 2011 and was continued in April 2012. The samples of the fish taken in the fish landing base in Krobokan, Semarang region. The total number of the fish samples taken as many as 30 fish, with the length between 35 cm to 70 cm and total weight ranged from 250 grams to 1600 grams. The results of the data analysis for the GSI values in both periods (October 2011 and April 2012) obtained between 5,583 % to 33,417 %. The values of Lm in the study period of October 2011 was 36,808 cm and in period of April 2012 was 26,927 cm. Diameter of fish eggs obtained from the both periods (October 2011 and April 2012) between 0,1 cm to 0,8 cm. Length and weight regression of fish in the October 2011 showed W=(0,0171)L2,691 and in the April 2012 showed W=(0,0234)L2,621. The values of condition factor in the October 2011 between 0,843 to 1,111 and in the April 2012 between 0,812 to 1,324.